Integration of warrior artificial intelligence and leadership reflexivity to enhance decision-making - Walter Matli (Applied Artificial Intelligence)
In the emerging literature on artificial intelligence (AI) and leadership, there is increasing recognition of the importance played by advanced technologies in decision-making. AI is viewed as the next frontier to improve decision-making processes and as a result enhance human decision-making in general. However, existing literature lacks studies on how AI, operating as a “warrior” or innovator in business, can in turn enhance leadership reflexivity, and thereby improve decision-making outcomes. This study is aimed at addressing this gap by drawing on the reflexivity perspective and existing research on AI and leadership to examine the integration of the concepts of warrior AI with leadership reflexivity to improve decision-making. The study used a systematic literature review to identify and map articles using specified inclusion and exclusion criteria to achieve this. Selected articles were included for in-depth analysis to address the issue under investigation. The study explored the potential benefits of blending advanced AI with reflective leadership strategies, offering insights into how organizations can optimize their decision-making processes through this innovative approach. A comprehensive literature review was thus the foundation for our investigation into how warrior AI may enhance human decision-making especially under high-stress conditions by providing real-time data analysis capabilities, pattern recognition skills, and predictive simulations. Our work emphasizes how leadership reflexivity plays a critical role in assessing AI-driven recommendations to ensure ethical soundness and contextual appropriateness of the decisions being taken. Based on our findings, we suggest that integrating AI capabilities with reflective leadership practices can lead to more effective and adaptable decision-making frameworks, particularly when swift yet well-informed action is necessary. This study adds to the existing body of knowledge by illustrating that, with the aid of a flow diagram, the integration of warrior AI into the reflective process can potentially amplify the benefits of AI, offering data-driven insights for leaders to reflect upon, thereby reinforcing the decision-making process with a more rigorous, ethical, and nuanced approach in alignment with organizational objectives and societal values. It is recommended that leadership actively engage in discussions regarding ethical AI use, ensuring alignment with organizational values and ethics. Ultimately, this study contributes valuable insights to discussions around AI and leadership by underscoring the significance of maintaining a balanced relationship between machine efficiency and human wisdom.